ممارسات إدارة الموارد البشرية الخضراء والميزة التنافسية - بلالي, أحمد; سملالي, يحضيه (University of Eloued جامعة الوادي, 2018)
ملخص: تهدف هذه الدراسة إلى تحليل وبلورة الإطار المفاهيمي لممارسات إدارة الموارد البشرية الخضراء وإبراز أثرها في تحقيق الميزة التنافسية المستدامة لمنظمات الأعمال، وذلك عبر مواءمة ممارسات إدارة الموارد البشرية مع الاستراتيجية البيئية للمنظمة. علما أن هذه الدراسة تستمد أهميتها بشكل أساسي من كونها من الدراسات القليلة التي ربطت بين ممارسات إدارة الموارد البشرية الخضراء والميزة التنافسية وبشكل يحقق المواءمة بين البعد البيئي والبعد الاقتصادي الذي يعتبر هدفا جوهريا لمنظمات الأعمال. ومن جهة أخرى فإنها تمثل قيمة مضافة في مجال الدراسات باللغة العربية التي تعتبر نادرة في هذا المجال. وقد اعتمدت منهجية الدراسة على مقاربة نظرية تحليلية لأدبيات إدارة الموارد البشرية الخضراء والميزة التنافسية، وتوصلت الدراسة إلى نتائج تؤكد على التأثير الإيجابي لممارسات إدارة الموارد البشرية الخضراء على الأداء البيئي والميزة التنافسية. Abstract: The objective of this study is to analyze and develop the conceptual framework for green human resource management practices and to highlight their impact on achieving the sustainable competitive advantage of business organizations by aligning human resources management practices with the organization's environmental strategy. This study derives its importance mainly from the fact that it is one of the few studies that have linked green human resource management practices to competitive advantage, in order to harmonize the environmental dimension with the economic dimension, which is a fundamental objective of business organizations. On the other hand, it represents benefit in the field of studies in Arabic, which are rare in this field. The methodology of the study was based on an analytical approach to the literature of green human resources management and competitive advantage. The study found a positive impact of green human resource management practices on environmental performance and competitive advantage
Green human resource management practice and competitive advantage
مجلة رؤى المجلد الثامن العدد الثاني
Keywords: إدارة الموارد البشرية الخضراء، الميزة التنافسية، الأداء البيئي، المنظور المرتكز على الموارد، المنظور المرتكز على الموارد الطبيعية.; Green Human Resource Management, Competitive Advantage, Environmental Performance, Resource Based View, Natural Resource Based View. Jel Classification Codes : O15